The Role of Government and the Private Sector in Reducing Unemployment Among Indigenous Papuans in Sorong Regency - Yance Baho; Haning, Moch. Thahir; Abdullah, Muh. Tang (KnE Social Sciences, 2025)
This study explores the collaborative efforts between the government and the private sector in addressing unemployment among Indigenous Papuans (OAP) in Sorong Regency. By analyzing policy initiatives, development programs, and private sector engagement, the research highlights the strategies employed to enhance employment opportunities for the local population. The study finds that effective coordination, targeted vocational training, inclusive recruitment practices, and investment in local economic sectors significantly contribute to reducing unemployment rates. Moreover, the active participation of indigenous communities in planning and implementation processes strengthens the sustainability of employment initiatives. This research emphasizes the importance of continuous collaboration, capacity-building, and socio-economic empowerment to ensure long-term positive outcomes for Indigenous Papuans.